(untitled) (Research, Society and Development, 2024)
This study aimed to assess the impact of modified cassava (Manihot esculenta Crantz) and taro (Colocasia sp.) starches on the rheological properties of homemade yogurt. Five treatments were tested: yogurt thickened with 0.5% (AM 0.5%) and 1% (AM 1%) cassava starch, yogurt thickened with 0.5% (AI 0.5%) and 1% (AI 1%) taro starch, and a control (yogurt without any thickener). The starches were subjected to physical modification and were incorporated into the yogurt, and then evaluated for rheological properties, apparent viscosity, texture, water retention capacity and syneresis. The result showed that the apparent viscosity was higher in yogurts produced with starches at all analysis speeds, however, the control treatment only showed significant differences with AM 0.5% and AI 0.5% (p<0.05). In the evaluation of firmness, syneresis, consistency coefficient (k), and flow index (n), yogurts made with starch exhibited the highest values, showing significant differences (p<0.05) compared to the control treatment. The water retention capacity (WHC) values ​​indicated significant differences between the control yogurt and the yogurt produced with thickeners, except AI 1% (p<0.05). For adhesiveness, no significant differences (p>0.05) were observed between starch and control treatments. The study concluded that modified cassava and taro starch improves the rheological properties of homemade yogurt, specifically in apparent viscosity, consistency, and firmness, and reduces the occurrence of syneresis.